Multimodalidade e contexto na leitura de textos charge - Souza, Lídia Lerbach de (2020)
With the popularization of the internet and digital technologies, communication becomes increasingly plural, varied, multimodal. The interaction between words and images expands the traditional notion of text and adds aspects such as images and colors, which demand a new way of reading. Therefore, this dissertation, linked to the line of research Text And Discourse in Oral and Written Modalities PUC-SP, has the theme of reading cartoons, understood as a genre of multimodal text, whose meaning is completed in the interaction between words and images. This genre attracts the attention of the reader due to the dynamic and humorous way in which it critically addresses the themes that move the country's political and social life. Furthermore, it is widely used in schools and in national exams and entrance exams, although textbooks do not indicate a specific metalanguage for reading cartoons. Due to this gap, the general objective is to contribute to linguistic studies about textual multimodality. As specific objectives, we chose: to verify how the multimodal textual composition, according to GDV, can contribute to the teaching of reading multimodal texts at school; examine the cognitive, social and language contexts in the construction of meaning when reading a journalistic cartoon; investigate how the cartoon builds ideological meanings for the text. The theoretical support that underlies this work and provides guidelines for the analysis of the corpus is based on the Grammar of Visual Design (GDV), by KRESS and van LEEUWEN (2006) and the Theory of Contexts by TEUN A. VAN DIJK (2012). The results indicate that the reading of the multimodal text requires analysis of the imagery landscape, as well as the contexts of the text. Therefore, the reading methodology employed in this study can be used to teach reading multimodal texts to which readers are exposed every day